Friedrich Engels, historical materialism and the Crimean War - Blackledge, Paul (Studies in East European thought, 2025)
This essay explores Friedrich Engels’ understanding of, and contribution to, historical materialism through the lens of his military writings. After unpacking the tacit theoretical architecture underpinning some of his encyclopaedia articles on the history of warfare, I move to focus on his analysis of the organization, culture and leadership of the various antagonists involved in the Crimean War (1853-1856). Notwithstanding the fact that Engels often wore his Marxism lightly when writing on military matters, I argue that these essays illuminate a sophisticated understanding of historical materialism that is quite at odds with those all too often repeated criticisms of his thought as a form of mechanical materialism and economic reductionism. Indeed, Engels’ writings on military organization during the Crimean War illuminate his dialectical understanding of the unity of essential and historical aspects of capitalist management; including powerful and nuanced analyses of national, class, ethnic and gendered subjectivities through which organizational cultures were reproduced in an (emerging) capitalist context. I show that while Engels understood that modes of production set parameters within which specific military forms emerged as (historically) necessary structures, he also laid great emphasis on the ways in which these organizations operated according to their own emergent principles and through specific cultures and concrete individuals. I submit that through these writings he made an important contribution to our understanding of military organization, and one that provides valuable historical context through which to understand more recent conflicts over the Crimean peninsula.